The Role of Parents in Preserving Local Language - Oktafianti, Nurul; Safira, Lailan; S, Ranti Fadila; Sit, Masganti (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Local languages are integral to cultural identity, linking generations to their ancestral history. Nevertheless, in the age of globalization, its existence can be endangered by the prevalence of national and foreign languages. Parents are crucial in safeguarding regional languages, particularly by integrating and familiarizing them into familial interactions. This research seeks to examine the methods by which parents contribute to the preservation of regional languages, their motivations for such efforts, and the obstacles they encounter. Data were gathered using a qualitative methodology, which included in-depth interviews, observations of family interactions, and literature reviews. The findings indicate that parents maintain the local language via daily dialogues, traditional songs, folklore, and internet platforms. Nonetheless, students encounter obstacles including the impact of national and foreign languages, insufficient environmental support, and restricted learning resources. Assistance from educational institutions and communities is essential to cultivate an atmosphere conducive to the acquisition of regional languages. This collaborative initiative not only maintains local languages but also fortifies the cultural identity of forthcoming generations. This research underscores the importance of synergy between families, schools, and communities in sustaining the nation's cultural wealth.